THE ROLE OF NOTARIES IN BANKING CREDIT AGREEMENTS: ANALYSIS OF LAWS NO. 10 OF 1998 AND NO. 2 OF 2014 - Rizal Ramadhani (Fox Justi : Jurnal Ilmu Hukum, 2021)
The position of a Notary, as a General Officer who makes an authentic deed is very much needed in banking business activities, one of which is in making a deed of banking credit agreement involving customers and banks, to guarantee the truth of the contents set forth in the banking credit agreement, so that the truth is not publicly disclosed. no doubt. The approach method is normative juridical, namely legal research conducted by reviewing and testing secondary data in the form of positive law. The research specification used is descriptive analytical, that is, systematically describes the facts and problems related to the role of a notary in banking credit agreements in the event that the debtor defaults in relation to Law no. 10 of 1998 jo. Law No. 2 of 2014 concerning changes to the position of a notary. Notaries are very important in helping to create legal certainty and protection for the community. This legal certainty and protection can be seen through the authentic deed made as perfect evidence in court. Whereas the role of a notary in the deed of banking credit agreement made notarial by a notary is very useful for creditors if the debtor defaults on the strength of the evidence. In banking practice, making credit agreements with private deeds can also provide execution guarantees because both notarial and private deeds are always followed by institutions with other guarantee institutions whose deeds are executorial such as APHT.